George R. Donnan, Annotated Code of Criminal Procedure and Penal Code of the State of New York as Amended 1882-85, at 172, tit. 12, § 410 (1885) - (:unkn) unknown (General Publisher, 1885)
Prohibited using or attempting to use, carrying, concealing, or possessing a slungshot, billy, sandclub or metal knuckles, or a dagger, dirk or dangerous knife. Punishable as a felony, and as a misdemeanor if a minor.
--
Keywords: POSSESSION - NON-GUN ARMS